Behold the monster : confronting America's most prolific serial killer - Lauren, Jillian (Sourcebooks, 2023)
"It all started when journalist Jillian Lauren asked LAPD Homicide Detective Mitzi Roberts about which case Roberts was most proud of closing. "Samuel Little," Roberts answered. The now 79-year-old Little had murdered approximately 90 women over six decades and repeatedly got away with the murders due to lack of evidence (or jurisdiction); Roberts finally brought him to justice by tying him to the murders of three Los Angeles women. Surprised she had never heard of Little, Lauren started digging. She started exchanging letters with Little until she got a face-to-face meeting that led to hundreds of hours of interviews full of information Little had never shared with law enforcement. Lauren knew this journey to the truth was taking its toll on her, but she couldn't stop--Little was giving her a powerful and harrowing window into the psyche of a serial killer. To balance out his darkness, Lauren decided to illuminate the lives of the women he killed. In her interviews, he confessed to 12 additional murders, supplying details that Lauren could share with families in need of closure. Harrowing, insightful, and extraordinarily adept at giving Little's victims a chance to have their stories heard for the first time, Behold the Monster is a true crime book as unforgettable as it is terrifying"--